ИЗБИРАТЕЛЬНОСТЬ ПИТАНИЯ ЛИЧИНОК КАЛКАНА И ВЫБОР СТРАТЕГИИ ИХ КОРМЛЕНИЯ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 1999)
Исследована избирательность питания личинок черноморской камбалы калкана (Psetta maeotiсa Pallas) в раннем онтогенезе (от 5 до 15 сут) в лабораторных условиях при использовании различных сочетаний жертв - культивируемого зоопланктона: коловраток (Brachionus plicatilis), науплиев и копеподитов гарпактикоидных (Tisbe furcata) и каланоидных (Acartia clausi) копепод. На 5 сутки личинки отбирали коловраток - из любого сочетания жертв, с 10 суток избегали их в присутствии копеподитов гарпактикоидных копепод, а с 15 суток активно выбирали ранних копеподитов каланоидных копепод. Оценку избирательности питания проводили по второму индексу элективности Ивлева (1977) - (Ei), на который на 5-10 сут влияла доступность жертвы, а с возраста 15 сут - пригодность. Рассмотрено влияние стратегии кормления личинок на получение молоди определенного типа.
Black Sea turbot larvae feeding selectivity and choice of feeding strategy
The changes of food preference of the Black Sea turbot (BST), kalkan (Psetta maeotiña Pallas) larvae during ontogenesis from 5 to 15 days after hatching were studied in laboratory using multiple prey assemblages including different ratios of prey types - cultivated zooplankton: rotifers (Brachionus plicatilis), nauplii and copepodites of harpacticoid (Tisbe furcata) and calanoid (Acartia clausi) copepods. The larvae day 5 selected primarily for B. plicatilis - in any prey combination, and start to avoid them only in the presence of early copepodites of T. furcata on day 10 and from day 15 - in the presence of early copepodites of A. clausi. Prey selectivities were quantified by means of the Ivlev’s (1977) second electivity indices (Ei). Ei were affected by prey availability on days 5-10 and by prey suitability - on day 15. Effect of feeding strategy on the type of rearing larvae is discussed.